Hierarchical metal-oxide nanostructures for high-performance supercapacitor electrodes - Guan, Cao (2013)
Rational construction of metal oxides materials with different functions into a proper integrated system represents a promising way to create next generation electrodes materials. In this thesis, we employed technologies for the rational design and facile construction of several metal oxide based hierarchical nanostructures for their application in electrochemical energy storage devices.